2010
DOI: 10.1107/s1600536810022725
|View full text |Cite
|
Sign up to set email alerts
|

(2E)-1-(2,5-Dichloro-3-thienyl)-3-(6-methoxy-2-naphthyl)prop-2-en-1-one

Abstract: In the title compound, C18H12Cl2O2S, the dihedral angle between the thio­phene ring and the naphthalene ring system is 2.13 (4)°. In the crystal, pairs of weak inter­molecular C—H⋯O hydrogen bonds form centrosymmetric dimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A survey of the Cambridge Structural Database (CSD, Version 5.39, last update November 2016; Groom et al, 2016) using (E)-3-(phenyl)-1-(2,5-dichlorothiophen-3-yl)prop-2-en-1-one as the main skeleton revealed the presence of three structures containing a similar 2,5-dichlorothiophene-chalcone moiety to the title compound but with different substituents on the terminal phenyl rings, viz. (Dutkiewicz et al, 2010), 3,4-dimethoxyphenyl (Harrison et al, 2010a) and 6-methoxy-2-naphthyl (Jasinski et al, 2010). In these three compounds, the dihedral angles between the central and terminal phenyl/naphthyl ring are in the range 2.13-11.90 .…”
Section: Database Surveymentioning
confidence: 96%
“…A survey of the Cambridge Structural Database (CSD, Version 5.39, last update November 2016; Groom et al, 2016) using (E)-3-(phenyl)-1-(2,5-dichlorothiophen-3-yl)prop-2-en-1-one as the main skeleton revealed the presence of three structures containing a similar 2,5-dichlorothiophene-chalcone moiety to the title compound but with different substituents on the terminal phenyl rings, viz. (Dutkiewicz et al, 2010), 3,4-dimethoxyphenyl (Harrison et al, 2010a) and 6-methoxy-2-naphthyl (Jasinski et al, 2010). In these three compounds, the dihedral angles between the central and terminal phenyl/naphthyl ring are in the range 2.13-11.90 .…”
Section: Database Surveymentioning
confidence: 96%
“…In recent years, chalcones have been used in the field of materials science as non-linear optical devices (Raghavendra et al, 2017;Chandra Shekhara Shetty et al, 2016). In view of all the above and as part of our ongoing work (Harrison et al, 2010;Jasinski et al, 2010;Dutkiewicz et al, 2010) herewith we report the crystal and molecular structure of the title compound.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Recently, chalcones have been used in the field of materials science as non-linear optical devices (Raghavendra et al, 2017;Chandra Shekhara Shetty et al, 2016). The crystal structures of (E)-1-(2,5-dichloro-3-thienyl)-3-[4-(dimethylamino)phenyl]prop-2-en-1-one (Dutkiewicz et al, 2010), (2E)-1-(2,5-dichloro-3-thienyl)-3-(6-methoxy-2-naphthyl)prop-2en-1-one (Jasinski et al, 2010), (E)-1-(2,5-dichloro-3-thienyl)-3-(3,4-dimethoxyphenyl)prop-2-en-1-one (Harrison et al, 2010a), (E)-3-(2-chloro-4-fluorophenyl)-1-(2,5-dichlorothiophen-3-yl)prop-2-en-1-one (Sanjeeva Murthy et al, 2018) and (2E)-3-(2,4-dichlorophenyl)-1-(2,5-dichlorothiophen-3-yl)prop-2-en-1-one (Murthy et al, 2018) have previously been reported.…”
Section: Chemical Contextmentioning
confidence: 99%